2007
DOI: 10.1039/b617995a
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of charge carrier injection into organic field-effect transistors by self-assembled monolayers of alkanethiols

Abstract: Manipulation of charge carrier injection into organic field-effect transistors by self-assembled monolayers of alkanethiols Asadi, Kamal; Gholamrezaie, Fatemeh; Smits, Edsger C. P.; Blom, Paul W. M.; de Boer, Bert

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 26 publications
4
99
0
Order By: Relevance
“…[6,20] In OFETs fabricated with carbon nanotubes [21] or amorphous polymer semiconductors, [22] modifying the work function of the electrodes with self-assembled monolayers (SAMs) has been shown to influence the OFET performance. In case of pentacene-(or in general crystalline organic semiconductors-) based OFETs with SAM-modified gate oxide and/or electrodes, however, changes in performance are accompanied by changes in the morphology of pentacene (or crystalline organic semiconductor) deposited onto the modified surface.…”
Section: Single-layer Pentacene Field-effect Transistors Using Electrmentioning
confidence: 99%
“…[6,20] In OFETs fabricated with carbon nanotubes [21] or amorphous polymer semiconductors, [22] modifying the work function of the electrodes with self-assembled monolayers (SAMs) has been shown to influence the OFET performance. In case of pentacene-(or in general crystalline organic semiconductors-) based OFETs with SAM-modified gate oxide and/or electrodes, however, changes in performance are accompanied by changes in the morphology of pentacene (or crystalline organic semiconductor) deposited onto the modified surface.…”
Section: Single-layer Pentacene Field-effect Transistors Using Electrmentioning
confidence: 99%
“…This work is based on the idea that this could eventually be achieved by inserting a self-assembled monolayer, i.e, a structure that is self-fabricated upon deposition, and could also modify the metal electrode's work-function and the charge carrier injection barrier, e.g., in an organic field effect transistor. 17 Recently, charge transfer complexes have been used in this context, 18,19 showing interesting effects on hole-injection barriers. More generally, self-assembly can lead to the formation of a wide range of twodimensional structures with different mechanical and electrostatic properties 20À22 and appears to be a very promising route for the nanofabrication of interlayers.…”
mentioning
confidence: 99%
“…First, a Dutch group reported on transistors made of MEH-PPV and regio-regular polyhexylthiophene (rr-P3HT) with gold electrodes modified by decanethiol SAMs with CH 3 and CF 3 end groups [28]. This time, TLM measurements indicated that the channel mobility only depends on the nature of the semiconductor, not on that of the contact.…”
Section: Morphological Vs Dipolar Effectsmentioning
confidence: 99%